INCREASING STUDENTS’ SPEAKING ABILITY THROUGH BOARD GAME AT THE EIGHTH GRADE OF SMP NEGERI 2 LAHEWA TIMUR IN 2022/2023 - Zalukhu, Oktavius; Harefa, Trisman; Waruwu, Yaredi; Daeli, Hidayati (Academy of Education Journal, 2023)
Speaking was one of the essential skills in language learning. It was necessary to communicated effectively in a language. When students speak English they do not explore their speaking skills because of a lack of knowledge in speaking. Therefore, to minimize students' speaking problems, the researcher apply board games as a medium to increase students' speaking ability. The purpose of the research is to increase the students’ speaking ability through Board Game at the eighth grade of SMP Negeri 2 Lahewa Timur which the total numbers of the students was 20 persons. The research was conducted by using Classroom Action Research (CAR) design. This research was applied into two cycles. Each cycle consisted of planning, action, observation, and reflection. The instruments used by the researcher to collect the data were observation sheet, test and field note. From the result of each cycle, the researcher finds that the students get an improvement in their speaking through Board Game. At the second meeting of cycle II the researcher obtained an increase in students, that students overall reached MCC (70).